ANALISA BRIKET BERBAHAN DASAR LIMBAH PRODUKSI SANDAL DAN TEMPURUNG KELAPA DENGAN VARIABEL KOMPOSISI DAN TEKANAN SEBAGAI ENERGI ALTERNATIF - Agung, Pramoda; Firmanto, Deta (MEKANIKA: Jurnal Teknik Mesin, 2015)
oblems. The worst happen is at the end of December 2014 within the rainy season, the area was flooded dueto the amount of waste that was caught in the river and gutters. To reduce the negative impact of huge amount ofwaste of production slippers. The author wants to attempt to recycle the waste into alternative energy ie briquettes.Briquettes made not only to reduce the negative impact arising from the accumulated waste sandals production, butalso can be used as an alternative energy fuel. In this case study, first, slipper's waste and a mixture of coconut shellthrough the pyrolysis process beforehand separately about 350-400ºC. Each of the process takes two hoursdepending on the amount of waste in the pyrolysis. Using adhesive from starch glue with a ratio of 10: 1, ie, 1000grams of a mixture of waste and 100 grams of glue. Variation of the components used are piled waste 20%,shell80% and piled waste 60%, shell 40% . Pressed using a manual hydraulic press machine with variations of pressureof 60 kg / cm², 80kg / cm², and 100 kg / cm². Based on the analysis results obtained that the briquettes with acomposition of 60% waste and 40% shell with a pressure of 100 kg / cm² has a calorvalue, long boil, the old ignitionand efficiency most good, with a total moisture content of 10.61%, volatile matter 6:52%, 3.77% ash content, fixedcarbon 79.10% . So when being compared with the existing standard can be quite feasible to used as alternativeenergy.Keywords : piled waste, pyrolisis, briquette